Monitoring of Virulence Factors and Metabolic Activity in Aggregatibacter Actinomycetemcomitans Cells Surviving Antimicrobial Photodynamic Therapy via Nano-Chitosan Encapsulated Indocyanine Green - Pourhajibagher, Maryam; Rokn, Amir Reza; Rostami-Rad, Mehdi; Barikani, Hamid Reza; Bahador, Abbas (Frontiers in Physics, 2018)
Aggregatibacter actinomycetemcomitans is an etiological agent that is frequently found in both chronic and aggressive periodontitis as well as peri-implantitis. In this study we evaluated the effects of antimicrobial photodynamic therapy (aPDT) as an alternative treatment modality by nano-chitosan encapsulated indocyanine green (CNPs/ICG) as a photosensitizer on the virulence features of cell-surviving aPDT against A. actinomycetemcomitans. Cell cytotoxicity effect of CNPs/ICG was evaluated on primary human gingival fibroblast cells. A. actinomycetemcomitans ATCC 33384 photosensitized with CNPs/ICG were irradiated with diode laser at wavelength of 810 nm for 1 min, following bacterial viability measurements. The biofilm formation ability, metabolic activity and antimicrobial susceptibility profiles were assessed for cell-surviving aPDT. The effect of aPDT on the expression of virulent gene (fieF), encoding Ferrous-iron efflux pump, was evaluated by quantitative real-time PCR. CNPs/ICG-aPDT resulted in the significant reduction of cell viability (91%), the biofilm formation capacity (53%), and metabolic activity (48%) of A. actinomycetemcomitans when compared to the control group (P < 0.05); As well as, fieF gene expression was downregulated (14.8-fold) after the strains were treated with aPDT. The virulence of A. actinomycetemcomitans strain is reduced in cells surviving aPDT with CNPs/ICG, and this may have potential implications of aPDT for the treatment of A. actinomycetemcomitans infections in periodontitis and peri-implantitis in vivo.